2019
DOI: 10.1038/s41598-018-37154-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Gray Matter Volume, Executive Function, and Insomnia: Gender Differences in Adolescents

Abstract: The cerebellum is an important region responsible for adolescent cognitive function and sleep, and their correlation is expected to show different patterns depending on age and gender. We examined the regional cerebellar gray matter volume (GMV), executive function (EF) and insomnia symptoms to identify their correlation and gender differences in adolescents. Data for a total of 55 subjects’ (M = 31, F = 24, 14.80 ± 1.39 years old) were analyzed. The correlations between cerebellar regional GMV and Wisconsin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 87 publications
(76 reference statements)
3
18
1
1
Order By: Relevance
“…Moreover, it has been previously shown that the sensorimotor domain is related to the anterior cerebellar lobe, while the cognitive domain corresponds to the posterior cerebellar region (Stoodley and Schmahmann, 2010). This particular finding is consistent with the observed co-activation of the anterior cerebellum with regions corresponding to the sensorimotor network represented by iCAP 10 (see also Shirer et al 2012) and Supplementary Table SI-1) Meanwhile, the inferior posterior lobe has been associated to the frontal gray matter, a well-known core area of executive function (Jung et al, 2019; Tiemeier et al, 2010). Altogether, these studies support our current findings on the preferential tendency of posterior and anterior cerebellum to persist in wakefulness and N2, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, it has been previously shown that the sensorimotor domain is related to the anterior cerebellar lobe, while the cognitive domain corresponds to the posterior cerebellar region (Stoodley and Schmahmann, 2010). This particular finding is consistent with the observed co-activation of the anterior cerebellum with regions corresponding to the sensorimotor network represented by iCAP 10 (see also Shirer et al 2012) and Supplementary Table SI-1) Meanwhile, the inferior posterior lobe has been associated to the frontal gray matter, a well-known core area of executive function (Jung et al, 2019; Tiemeier et al, 2010). Altogether, these studies support our current findings on the preferential tendency of posterior and anterior cerebellum to persist in wakefulness and N2, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Although more attention should be given to children and adolescents, who have developing brains, most neuroimaging studies on sleep problems have focused on adults or patients with sleep problems 33 . However, it is known that general demographic factors (e.g., age, sex) profoundly influence the structure of the brain 34 .…”
mentioning
confidence: 99%
“…FDR thresholding controls the expected proportion of false positives only among brain regions showing significance 78 . Although conservative levels of FDR (e.g., 0.01-0.05) can be used in neuroimaging studies, FDR control levels in the range of 0.1-0.2 are originally and practically known to be acceptable and have been applied in several neuroimaging studies 33,78,79,88,89 . FDR corrected p-values were calculated by using spm_P_FDR.m with all regional p-value inputs, which is a MATLAB code included in the SPM toolbox.…”
mentioning
confidence: 99%
“…The grey matter of the corresponding brain region has been shown to increase during training [20,64]. The increased grey matter of the hippocampus, DLPFC, and cerebellum are associated with better performance in reference and working memory [64,65].…”
Section: Discussionmentioning
confidence: 99%